Measuring the carbon intensity of the South African economy - Arndt, Channing; Davies, Rob; Makrelov, Konstantin; Thurlow, James (Wiley, 2013)
We estimate the carbon intensity of industries, products and households in South Africa using data from a high resolution supply‐use table. Direct and indirect carbon usage is measured using multiplier methods that capture inter‐industry linkages and multi‐product supply chains. Carbon intensity is found to be high for exports but low for major employing sectors. Middle‐income households are the most carbon‐intensive consumers. These results suggest that carbon pricing policies (without border tax adjustments) would adversely affect export earnings, but should not disproportionately hurt workers or poorer households. Seven percent of emissions arise through marketing margins, implying that carbon pricing should be accompanied by supporting public policies and investments.